Modeling E-Payment Adoption and its Impact on MSME Financial Inclusion in North Kolaka - Bohari, Nurul Aulia; Firdaus, Firdaus; Puspita, Ulva Mega (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economic development; however, the adoption of e-payment systems in North Kolaka Regency remains relatively low. This study aims to model and analyze the adoption dynamics of e-payment among MSMEs using an SEIR (Susceptible-Exposed-Infected-Recovered) framework. Based on survey data from 485 MSMEs, simulations were conducted using Python to determine the spread and sustainability of adoption behavior. The results reveal that a majority of MSMEs are still unfamiliar with e-payment systems, while the proportion of active users remains limited. The numerical simulation yields a basic reproduction number of R₀ = 0.4939, indicating that e-payment adoption has not yet reached a sustainable level. To enhance the growth of e-payment usage and strengthen financial inclusion, policy strategies should focus on improving digital financial literacy, providing continuous incentives, and integrating MSMEs into broader go-digital programs.